Extreme ultraviolet laser ionization mass spectrometry: probing materials at the micro and nano scales - Rush, Lydia Alexandra, author; Menoni, Carmen S., advisor; Duffin, Andrew M., advisor; Farmer, Delphine K., committee member; Marconi, Mario C., committee member; Rocca, Jorge J., committee member (Colorado State University. Libraries, 2023)
The focus of this dissertation is the use of 50 to 10 nanometer wavelength extreme ultraviolet (EUV) laser light as a next generation probe for mass spectrometry analyses at the micro (>100 nanometers) and nano (≤100 nanometer) spatial scales. While the unique properties of EUV light have revolutionized the semiconductor industry through nanoscale lithography fabrication, the use of EUV lasers with analytical instruments, like mass spectrometers, for high spatial resolution chemical analyses is a relatively untapped area. This unexplored territory is owed partly to only recently bringing EUV lasers to an accessible "bench-top" scale. Herein I show how EUV laser ionization can be used with different types of mass spectrometers as a new route for interrogating nuclear and geologic materials with micro and nano scale lateral spatial resolution. I focus on the application of a compact capillary discharge EUV laser operating at a wavelength of 46.9 nanometers connected to a time-of-flight (TOF) mass spectrometer, called the EUV TOF. I also show for the first time how the 46.9 nm EUV laser ionization source can be connected to a commercial magnetic sector mass spectrometer, called the EUV magnetic sector. Specifically, I demonstrate that the EUV TOF instrument can measure the 235U/238U isotope ratio in 100 nm sized pixels in a heterogeneous uranium fuel pellet that was made by blending different feedstocks together. The results show that the EUV TOF maps similar micrometer sized areas of 235U/238U heterogeneity as nanoscale secondary ionization mass spectrometry (NanoSIMS), indicating that EUV laser ionization can be used to accurately probe complex nuclear materials within the scope of the study. I also show that the EUV TOF can be used to measure 206Pb/238U and 232Th/238U isotope ratios at the 8 µm scale in select geologic matrices of silicates, zircons, monazites, and iron manganese within error (±2σ) using a single non-matrix matched calibration standard. However, the precision on the ratio measurements was low for useful geologic applications, ranging between 1-10% at elemental concentrations exceeding hundreds of ppm because of the limitations of using a TOF for isotope ratio measurements. To this end, I show the current development of the new EUV magnetic sector instrument that uses the EUV laser ionization source with a commercial double-focusing sector-field multi-collector mass spectrometer with the aim of achieving more precise (<1%) and sensitive (≤ppm) isotope ratio measurements at high spatial scales (<10 µm down to the nanoscale). The EUV magnetic sector is being developed to probe more complex isotopic systems in nuclear and geologic materials that was not possible with the TOF mass spectrometer. The work here shows that the 46.9 nm wavelength EUV laser ionization source can be interfaced with Thermo Fisher's commercial sector-field multi-collector mass spectrometer called the Neptune by removing its inductively coupled plasma (ICP) region. The Neptune's ion optics, electric sector, and magnetic sector were modified for acceptance of the pulsed EUV-generated ions. These modifications resulted in ions from ≤2 µm diameter craters created by EUV laser ablation and ionization being successfully focused, separated by mass, and detected using the Neptune's electron multipliers. However, further system upgrades to the Neptune's detectors are needed for accurate isotope ratio measurements at high spatial scales because the 10 to 30 nanosecond wide EUV-generated ion pulses are on the order of the electron multipliers' dead time. With proper detectors, the EUV magnetic sector's accuracy, precision, sensitivity, efficiency, and spatial resolution can be measured in future experiments. The demonstration of the EUV magnetic sector instrument here represents the first time that an EUV laser ionization source has been used with a sector-field mass spectrometer, paving the way for future high spatial resolution isotope ratio analyses.
Keywords: isotopic analysis; nanoscale; mass spectrometry; extreme ultraviolet laser